In Vivo Evaluation of Cefuroxime Axetil-Loaded Bioadhesive Nanoparticles to Treat Haemophilus influenzae-Induced Otitis Media - Lin, Hong; Jia, Yizhen; Kong, Xiaohan; Wang, Shiting; Liu, Xiangyou; Liu, Yang; Deng, Yang (Frontiers in Bioengineering and Biotechnology, 2022)
Otitis media (OM) is a common disease in children. One of the most common pathogens causing OM is Haemophilus influenzae (NTHi). NTHi in the middle ear can be successfully eradicated by a regimen of oral antibiotics sustained for 7-10 days (e.g cefuroxime axetil 250 mg/day for patient 3 months to 2 years and 500 mg/day for patients ages ≥ 2 years). However, lack of compliance is relevant to treatment failure or early relapse. In order to overcome these challenges, we have developed antibiotics loaded bioadhesive nanoparticles (BNPs) that can adhere on the epidermis of the middle ear after local administration and significantly prolong the release time of antibiotics in the middle ear. Compared with oral administration of CA, local delivery of free antibiotic cefuroxime axetil (CA), and CA loaded non-bioadhesive nanoparticles (CA/NNPs), BNPs loaded with cefuroxime axetil (CA/BNPs) showed significantly longer retention time in the middle ear, resulting in continuous release of the drug and higher therapeutic efficacy against OM with only single dosage. CA concentrations were maintained above the minimum inhibitory concentration (MIC) for NTHi throughout 7 days’ treatment. NTHi OM in a mouse model was successfully eradicated without causing tissue toxicity. CA/BNPs minimizes systemic drug exposure through local administration, as demonstrated by undetectable levels in the blood.